The Development of Customer Loyalty Model for Mobile Travel Agent Application - Prihartono, Budhi; Ashari, Muhammad Azhar; Rizkiana, Aldila (Department Industrial Engineering, University of Muhammadiyah Malang, 2020)
The growth of smartphone users in Indonesia opens up business opportunities for service providers, in particular via m-commerce. However, along with these great opportunities and rivalry, service providers are required to make consumers faithful to the products and services they deliver. This research aimed to develop a conceptual model for an application based on m-commerce, particularly in the context of the mobile travel agent application. The research model was based on the application of five dimensions of mobile service quality (M-S-QUAL), customer engagement, and commitment as the predecessor factors of customer loyalty. The study was conducted on 760 MTA application users who participated in an online survey. The data were divided into two groups based on the level of income to be further analyzed using the Multigroup Structural Equation Modeling (SEM). The Multigroup SEM analysis showed that the concept of customer loyalty was explained differently by the two groups with different income levels.